Thermodynamic and structural investigations on mixing behavior of hetero-coordinated Al-based alloys in the fusion state - Koirala, I; Singh, BP; Jha, IS (BIBECHANA, 2015)
We have used simple statistical model to report the hetero-coordination of two Al- based liquid alloys, i.e. Al-Ge and Al-Fe at temperatures 2000K and 1873K respectively. Through thermodynamic functions such as free energy of mixing and ratio of activity of the component atoms of the alloys, we have reported the information on the interaction, stability and bonding strength among the constituent atoms in the alloys. At the microscopic level, concentration fluctuation in the long wavelength limit and Warren-Cowely short range order parameter help to obtain the microscopic information on structure of molten alloys. Our theoretical analysis is based on interchange or ordering energy parameter which is found to be negative and temperature dependent. Negative deviation from Raoultian behaviour is observed in the computed thermodynamic and structural parameters of the alloys. The computed results are in good agreement with experimental data. The analysis concluded that both alloys are of weakly interacting and chemically ordered system. BIBECHANA 13 (2016) 87-93